Pengaruh Profitabilitas, Likuiditas, Leverage Terhadap Yield Obligasi Syariah dengan Rating Obligasi Syariah sebagai Intervening - Titin Hartini; Sri Delasmi Jayanti (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
This study aims to examine the effect of profitability as proxied by ROE (Return on Equity), and Liquidity as proxied by CR (Current Ratio) and Leverage which is proxied by DER (Debt to Equity Ratio) on Bond Yield (Yield to Maturity) with Rating Bonds as an intervening variable in companies listed on the IDX (Indonesia Stock Exchange) for the 2016-2018 period. The type of research is quantitative research, with secondary data obtained from www.ibpa.co.id, www.pefindo.com, www.idx.go.id. The total sample is 10 companies that issued 61 Islamic bonds in the 2016-2018 period. The data analysis technique used is the path analysis test and data processing using SPSS 22 for windows. Research results Profitability has no effect on bond ratings, while Liquidity and Leverage have an effect on bond ratings. On profitability, liquidity and leverage affect the yield of Islamic bonds. In its mediation, the bond rating does not mediate between profitability and bond yield. Meanwhile, Liquidity and Leverage on Yeild bonds mediate through bond rating.